Development of Reading Literacy Culture in Elementary School Age Children in The Pekunden Flats in Semarang During the New Normal Period - Indrawan, Muhamad Fahrizal; Suharso, Putut (Edulib, 2024)
The low level of literacy that occurs among elementary school age children, especially in Indonesia, means that they still lack knowledge of the importance of literacy culture itself. Children from as early as possible should be given knowledge about the importance of literacy. This research discusses about the understanding and development of reading literacy culture among elementary school age children in the Pekunden Flats in Semarang during the period new normal. This research used qualitative method and with a case study approach. The method for taking informants uses the method purposive sampling, while the data collection technique uses interview, observation, and document techniques. The outcomes of the research show that elementary school age children in Pekunden Flats have increased their interest in reading during new normal compared to before during the pandemic era, there was a very significant decline in interest in reading. This is caused by several factors, including changes in the system of teaching and learning activities, government policies, and understanding of the culture of reading literacy in children which is influenced by internal and external factors. Internal factors include awareness of oneself, parents and family. External factors include the social environment, globalization, community and school environment.